Freedom on Social Networks: Threats and Coercion in Light of Article 20.1 of the Spanish Constitution - Martínez Cristóbal, Daniel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The enormous growth of the Internet in recent decades has led to the emergence of numerous online dangers, leaving victims increasingly exposed. The prevalence of crimes such as harassment, threats, and coercion on social media continues to rise, with the anonymity of perpetrators facilitating these offences. As a result, victims often experience heightened feelings of helplessness and fear for their safety, unable to identify or verify the authenticity of the threats or coercion they face. There is an urgent need to implement measures aimed at preventing these behaviours while also regulating anonymity on social media, ensuring that such measures fundamentally respect the right to freedom of expression. Addressing this evolving social reality within the digital context is crucial for the effective regulation of crimes occurring on social networks. It is essential to establish safe spaces for victims and prevent the recurrence of criminal behaviour on these platforms.